Ooooooooooookay then. I presume these are simultaneous?

The bottom equation is already solved for v, so substitute this into the other equations:

v = 180 - (240 - y) = y - 60

z = (90-x)

w = (120-y)

y = (180-x)

x = (120 - [y - 60]) = 180 - y

The w equation is already solved for w so substitute this into the others (which don't depend on w anyway):

v = y - 60

w = 120 - y

y = (180-x)

x = 180 - y

Again, the x equation is already solved for x so:

v = y - 60

w = 120 - y

x = 180 - y

y = (180 - [180 - y]) = y

So any value of y solves this. So your solution set is:

v = y - 60

w = 120 - y

x = 180 - y

and y is any number.

-Dan